THE ROLE OF PERSONNEL ASSESSMENT IN THE PROCESS OF HUMAN RESOURCE MANAGEMENT - A. Borshcheva; E. Kuzmina; I. Soklakova (Вестник университета)
The article considers the methods of personnel assessment in modern Russian and foreign companies, such as the method of management by objectives, performance management, method of personnel assessment «360 degrees», «assessment center». «As-sessment сenter» has studied in more detail. This method is a set of procedures that de-termines the success of a person in the professional sphere, the parameters of which have been laid down by the competence model. This method has proved itself as a powerful stimulating factor in the training of workers. Its peculiarity consists in the individual ap-proach, which determines the interest of respondents in training. At the same time, the evaluator can show the employee his hidden potential and possible growth zones. At pres-ent time, it is necessary to search new innovative approaches to personnel assessment.